Determinants of Rural Youths’ Participation in the Process of Social Innovations - Zajda, Katarzyna (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2016)
The aim of implementing social innovations is to eliminate the existing social problems, including problems of groups that are discriminated against. Contemporary youths are definitely a group which is disfavoured on the labour market. The objective of this paper is to point out the potential determinants of rural youths’ participation in the process of social innovations. The analysis focuses on selected components of the participants’ human and social capital, which may be important for their participation in social innovations. The paper presents the results of sociological research (involving the auditorium survey technique) carried out in the period 2014–2015 in Wielkopolskie Voivodeship, among young people aged 16–19 residing in rural areas. The participants attended upper secondary schools (vocational schools, secondary technical schools and general secondary schools). The performed analyses led to the identification of components of youths’ human and social capital which may have a negative influence on their participation in social innovations. First, young people have little knowledge on innovations, including social innovations, while such knowledge is especially valuable for future social innovators (also those who follow good examples in this regard) or pioneers of adopting social innovations in local conditions. Secondly, young people display little interest in local matters, which limits the possibility of their participation in social innovations implemented by local entities. Thirdly, youths’ social activity is only limited to school environment, which means that after graduation they may not continue that activity and thus not belong to networks in which social innovations are developed, implemented and adopted.
Keywords: social innovations; rural youth; human capital; social capital